(untitled) (Revista Contexto & Saúde, 2023)
Background: Using the support of a handrail during cardiopulmonary exercise testing (CPET) may alter physiologic parameters. The purpose is investigate the effects of handrail usage during the CPET in the metabolic parameters outcomes of young adults. Material and Methods: 39 young adults (age in years, 20.8 ± 2.9) of both sexes, 17 woman and 22 men performed two treadmill CPET on Ellestad protocol, in non-consecutive days. The first (T1) offered access to the support of a handrail; after 7 days, the second (T2) was performed without it. Differences between protocols for metabolic variables were compared using paried the t-test and repeated measures ANOVAS with interaction. Results: Regardless of sex, all participants exhibited superior results of metabolic parameters at T2 in contrast to T1. During T2, there was a major perception of respiratory and muscular effort, as well as a higher respiratory quotient for both sexes. When comparing T1 with T2, the VE/VCO2 slope was also significantly higher for women (29.31 ± 4.7 and 27.27 ± 4.53). For both sexes, when comparing the tests by stages, it was observed in stages 2, 3 and 4 higher values in the metabolic parameters for T2. The percentile difference for both sexes was 17% higher in S3 for women (T1=26.20±4.1 ml.kg-1.min-1;T2 28.79±4.2 ml.kg-1.min-1) and men (T1= 40.07±6.6 ml.kg-1.min-1; T2 45.92±4.8 ml.kg-1.min-1).Conclusion: The holding of the handrail attenuated the participants’ cardiorespiratory and metabolic responses by more than 15% during CPET. Material and Methods: 39 young adults (age in years, 20.8 ± 2.9) of both sexes, 17 woman and 22 men performed two treadmill CPET on Ellestad protocol, in non-consecutive days. The first (T1) offered access to the support of a handrail; after 7 days, the second (T2) was performed without it. Differences between protocols for metabolic variables were compared using paried the t-test and repeated measures ANOVAs with interaction. Results: Regardless of sex, all participants exhibited superior results of metabolic parameters at T2 in contrast to T1. During T2, there was a major perception of respiratory and muscular effort, as well as a higher respiratory quotient for both sexes. When comparing T1 with T2, the VE/VCO2 slope was also significantly higher for women (29.31 ± 4.7 and 27.27 ± 4.53). For both sexes, when comparing the tests by stages, it was observed in stages 2, 3 and 4 higher values in the metabolic parameters for T2. VO2 was approximately 17% higher at T2, stage 3, for women and men. Conclusion: The holding of the handrail attenuated the participants’ cardiorespiratory and metabolic responses by more than 15% during CPET.